Guided Inquiry Learning Module with Multimedia Assisted on Cell Metabolism for XII Grade of Senior High School - Mochammad Ali Mashur; Mohamad Amin; Umie Lestari (Jurnal Pendidikan Sains, 2018)
Abstract: The aim of this development research was to determine the validity, effectiveness, and practicality of the guided inquiry learning module assisted by multimedia on cell metabolism. This study adapted the research and development from Lee and Owen model. The validity of modules and multimedia as a product is known from the validation scores of experts, while the practicality is known from biology teacher and student responses, and the effectiveness from student learning outcomes. The results showed that the average module expert validation score was 89.67% (very valid), material experts were 100% (very valid), media experts were 96.67% (very valid) and field practitioners were 87.50 (valid). Most students gave a positive response to the module by 85.08% and on the media 80,56%. The effectiveness of the development module produces a value of p = 0.13 which means that it can significantly improve student learning outcomes. Based on these results, it can be concluded that the guided inquiry learning module with mutimedia assisted on cell metabolism is valid, effective, and practical so that it can be used more continued on XII grade senior high school students.Key Words: module, guided inquiry, multimedia, cell metabolismAbstrak: Tujuan penelitian pengembangan ini adalah untuk mengetahui kevalidan, keefektifan, dan kepraktisan modul belajar inkuiri terbimbing berbantuan multimedia pada materi metabolisme sel. Penelitian ini mengadaptasi model penelitian & pengembangan Lee dan Owen. Kevalidan modul belajar dan multimedia sebagai produk diketahui dari skor validasi para ahli, sedangkan kepraktisan diketahui dari respon guru biologi dan siswa, sedangkan keefektifan diketahui dari hasil belajar siswa. Hasil penelitian menunjukkan bahwa rerata skor validasi ahli modul sebesar 89,67 % (sangat valid), ahli materi sebesar 100 % (sangat valid), ahli media sebesar 96,67 % (sangat valid) dan praktisi lapangan sebesar 87,50 (valid). Sebagian besar siswa memberikan respons positif terhadap modul sebesar 85,08 % dan terhadap media 80,56%. Efektivitas modul pengembangan menghasilkan nilai p = 0,13 yang artinya secara signifikan dapat meningkatkan hasil belajar siswa. Berdasarkan hasil tersebut, dapat disimpulkan bahwa modul belajar inkuiri terbimbing berbantuan multimedia pada materi metabolisme sel yang dikembangkan tergolong valid, efektif dan praktis sehingga dapat digunakan lebih lanjut pada siswa kelas XII SMA.Kata kunci: modul, inkuiri terbimbing, multimedia, metabolisme sel